KEMANDIRIAN EKONOMI RUMAH TANGGA MELALUI AFFILIATE TIKTOK SHOPE DALAM PERSPEKTIF MAQASHID SYARIAH DI JEMBER - Nabila Zahrotul Ula; Siti Aimatul Mujahida; Aminatus Zahriyah (CENDEKIA: Jurnal Ilmu Pengetahuan, 2026)
ABSTRACT The development of the digital economy has led to the emergence of various platform-based income schemes, including the TikTok Shop affiliate program utilized by households. This phenomenon is important to examine as it relates not only to income generation but also to how such income is utilized to strengthen household economic independence. Previous studies have primarily focused on marketing and economic empowerment aspects, with limited attention to its impact on household economic independence from a maqashid sharia perspective. Therefore, this study aims to analyze the role of TikTok Shop affiliates in promoting household economic independence in Jember Regency using the maqashid sharia framework. This study employs a descriptive qualitative approach, using primary data from in-depth interviews supported by secondary data from relevant literature. Data were analyzed through data reduction, classification of needs based on dharuriyat, hajiyat, and tahsiniyat categories, and conclusion drawing. The results indicate that income from affiliate activities is utilized hierarchically to fulfill these categories of needs, thereby contributing to strengthening household economic independence. The findings conclude that TikTok Shop affiliate practices have the potential to align with maqashid sharia principles and support sustainable household economic development within the digital economy context. ABSTRAK Perkembangan ekonomi digital mendorong munculnya berbagai skema pendapatan berbasis platform, termasuk program affiliate TikTok Shop yang dimanfaatkan oleh rumah tangga. Fenomena ini penting dikaji karena berkaitan tidak hanya dengan peningkatan pendapatan, tetapi juga dengan pola pemanfaatannya dalam membangun kemandirian ekonomi keluarga. Kajian terdahulu umumnya menyoroti aspek pemasaran dan pemberdayaan ekonomi, namun masih terbatas dalam menganalisis dampaknya terhadap kemandirian ekonomi rumah tangga dalam perspektif maqashid syariah. Oleh karena itu, penelitian ini bertujuan menganalisis peran affiliate TikTok Shop dalam mendorong kemandirian ekonomi rumah tangga di Kabupaten Jember dengan menggunakan kerangka maqashid syariah. Penelitian ini menggunakan pendekatan kualitatif deskriptif dengan data primer melalui wawancara mendalam dan didukung data sekunder dari literatur terkait. Analisis dilakukan melalui reduksi data, pemetaan kebutuhan berdasarkan kategori dharuriyat, hajiyat, dan tahsiniyat, serta penarikan kesimpulan. Hasil penelitian menunjukkan bahwa pendapatan dari aktivitas affiliate dimanfaatkan secara berjenjang untuk memenuhi ketiga kategori kebutuhan tersebut, sehingga berkontribusi terhadap penguatan kemandirian ekonomi rumah tangga. Simpulan penelitian menegaskan bahwa praktik affiliate TikTok Shop berpotensi selaras dengan prinsip maqashid syariah dan mendukung keberlanjutan ekonomi rumah tangga dalam konteks ekonomi digital.